WATER PHASE CONCENTRATE SOLUBILITY TEST SNAKEHEAD FISH EXTRACT (Channa Striata) IN ORGANIC COSOLVENT - Mohamad Andrie; Wintari Taurina (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Snakehead fish extract has been recognized for its potential in healing postoperative wounds and burns. The extract contains albumin, which aids in tissue formation and healing processes. To create a high-quality wound healing drug, the extract needs to be formulated into a concentrated form and combined with a solvent that can effectively dissolve its active substances. Understanding the solubility profile of the extract and the composition of the solvent is crucial for this purpose. This study aims to determine the solubility profile of the aqueous phase concentrate of snakehead fish extract in an organic co-solvent. Solubility is an important parameter as it can impact the release rate and therapeutic effectiveness of the drug. A solubility test was conducted to assess the solubility of the aqueous phase concentrate in various solvents. The results of the solubility test indicated that the aqueous phase concentrate of snakehead fish extract exhibited good solubility in aquadest (20%), slight solubility in propylene glycol (8.5%) and honey (2%), and was insoluble in ethanol, glycerin, mannitol, and sorbitol (0%). These findings provide valuable information for formulating the extract into a wound healing drug with an appropriate solvent composition, ensuring optimal solubility and therapeutic efficacy according to pharmacopeial standards. Keywords: Concentrate; Aqueous phase of snakehead fish extract; Solubility; Solvent; Polarity Properties